The Impact and Adaptation of Bank to the Marriage Equality Law for the LGBTQ Community in Phitsanulok Province - Chamlongkun, Chatri; Klincharoen, Yatipichai; Dansawang, Thitivat; Jaidee, Anusorn; Sittijuk, Pramote (Journal of Dhamma for Life, 2025)
This research aimed to 1) examine the impacts and adaptation strategies of banks in Phitsanulok Province in response to the enforcement of the Marriage Equality Act from the perspectives of bank executives and staff, and 2) investigate the satisfaction of LGBTQ customers regarding the banks’ adaptation to the enforcement of the Marriage Equality Act in Phitsanulok Province. The sample consisted of 15 managers and assistant managers from four main branches of Kasikornbank in Phitsanulok Province, and 384 LGBTQ customers selected by convenience sampling. The research instruments included a semi-structured interview guide to study the impacts and adaptation strategies of the banks, and a questionnaire to assess LGBTQ customers’ satisfaction with the banks’ adaptation. Data were analyzed using content analysis, frequency, percentage, mean, and standard deviation. The results showed that the banks were affected by the Marriage Equality Act in various aspects, such as joint account opening, joint loan applications, life insurance purchases, and documentation related to gender identity. Consequently, banks adapted in four main areas, with cognitive adaptation being the most significant. LGBTQ customers’ satisfaction with the banks’ adaptation was generally high, especially in the area of relationships, where banks fostered trust and provided friendly services. The findings highlight the importance of banks’ attitude and policy adjustments to appropriately support LGBTQ customers and recommend ways to improve services to enhance satisfaction and equality in the future.